How Well Does the Traffic System Protect Transit from Congestion? Measuring Route-Level Costs That Congestion Imposes on Transit Operators and Users - Peter G. Furth; Ahmed T. M. Halawani (Journal of Advanced Transportation)
As transit agencies and road owners adopt the objective of protecting transit from congestion, it becomes important to have a method for measuring the cost that congestion imposes on transit. Congestion impacts transit both by lowering average speed and by increasing service unreliability. Altogether, five congestion impacts were identified: increased running time and recovery time for transit operators and increased riding time, waiting time, and buffer time for passengers. A methodology for estimating those impacts was developed using automatic vehicle location data. The basic approach was to compare the impact variables during various periods of the week against a base period when there is no congestion (late night and early morning), making adjustments to account for differences in demand that affect running time apart from congestion. The methodology was successfully applied to a sample of 10 bus routes in the Boston area. The cost of congestion on the sample routes was found to range from $1 to $2 per passenger, with annual costs as great as $8 M per year on some routes. Of the total congestion cost, just under 20% applies to the operator, with the remainder applying to passengers. And while the operator is mainly affected by increased average delay, passengers are mainly affected by worsening service reliability.